Straight and narrow compassion and clarity in the homosexuality debate - Schmidt, Thomas E. (Leicester UK IVP, 1995)
Includes bibliographcial references and indexes.
Keywords: Homosexuality -- religious aspects -- Christianity; Homosexuality -- ethics; Homosexuality -- Biblical teaching